Some Structures on Pythagorean Fuzzy Topological Spaces - Taha Öztürk; Adem Yolcu (Journal of New Theory, 2020)
In this paper, we introduced some operations such as Pythagorean fuzzy interior, Pythagorean fuzzy closure, Pythagorean fuzzy boundary, Pythagorean fuzzy basic on Pythagorean fuzzy topological spaces. Also, the notions of Pythagorean fuzzy open (closed) functions and Pythagorean fuzzy homeomorphism are introduced, and their basic properties are investigated., , , , , .